2021
DOI: 10.1088/1742-6596/1973/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

FPGA Realization of ANFIS Controller Using a Proposed Digital Design

Abstract: The design and realization of Adaptive Neuro-Fuzzy Inference System (ANFIS) controller based on Field Programmable Gate Array (FPGA) is presented in this paper. The controller intended to control the temperature of medical oven. A novel design of digital ANFIS is presented here for the implementation process. Different controllers are designed and their results are compared using MATLAB program to show the ANFIS superiority. The designed controllers tested for cell cultures application at 37.5. A reduction is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…To provide fault tolerance, Cobleigh et al presented tree -structured self-adaptation models for such mobile robots (13). In response to observed conditions, Gafni et al [1] presented an architectural style for real-time systems in which dynamic reconfiguration is implemented via a synchronous control task (14). The author has proposed comparison of various Biological Inspired algorithms the navigation over static and dynamic condition is analysed (for single and multiple robot systems) and it has been observed that the reactive approaches are more robust and perform well in all terrain when compared to classical approaches (15).…”
Section: Literature Surveymentioning
confidence: 99%
“…To provide fault tolerance, Cobleigh et al presented tree -structured self-adaptation models for such mobile robots (13). In response to observed conditions, Gafni et al [1] presented an architectural style for real-time systems in which dynamic reconfiguration is implemented via a synchronous control task (14). The author has proposed comparison of various Biological Inspired algorithms the navigation over static and dynamic condition is analysed (for single and multiple robot systems) and it has been observed that the reactive approaches are more robust and perform well in all terrain when compared to classical approaches (15).…”
Section: Literature Surveymentioning
confidence: 99%
“…The use of neural networks is widespread in scientific literature and engineering practice. Abbas Issa et al(Issa et al, 2021) presented a reconfigurable insightful controller for mobile robots. Programming known as reconfigurable control framework, was used to modify the structure of the control system, and the FPGA chip was used in the planning and implementation of the controller.…”
mentioning
confidence: 99%